Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I cannot find the following limit: $$ \lim_{x\to 0} \frac{1-\cos x \cos(2x)}{x^2} \, . $$ Please, help me.

share|improve this question
    
Apply l'Hopital's rule! –  Atul Ingle Oct 15 '12 at 21:08

4 Answers 4

up vote 2 down vote accepted

This can be evaluated by applying L'Hôpital's Rule twice. We have:

$$\lim_{x \to 0} \left(\frac{1-\cos x \cos(2x)}{x^2}\right) = \ldots, $$ $$= \lim_{x \to 0} \left(\frac{\sin x\cos(2x)+2\cos x\sin(2x)}{2x}\right), $$ $$= \lim_{x \to 0} \left(\frac{5\cos x \cos(2x)-4\sin x\sin(2x)}{2}\right),$$ $$ = \frac{5}{2} \, . $$

share|improve this answer

$$\cos(x) \cos(2x) = \left(1 - \dfrac{x^2}{2!} + \dfrac{x^4}{4!} - \cdots \right)\left(1 - \dfrac{(2x)^2}{2!} + \dfrac{(2x)^4}{4!} - \cdots \right)\\ = 1 - \dfrac{x^2 + 4x^2}{2!} + \mathcal{O}(x^4)$$ Hence, $$1 - \cos(x) \cos(2x) = \dfrac52 x^2 + \mathcal{O}(x^4)$$ Can you now find the limit?

EDIT Alternately, you could also proceed as below.

$$\cos(x) \cos(2x) = \cos(x) \left(2 \cos^2(x)-1 \right) = 2 \cos^3(x) - \cos(x)$$ Hence, $$1- \cos(x) \cos(2x) = 1 + \cos(x) - 2\cos^2(x) = (1-\cos(x))(1+2\cos(x) + 2\cos^2(x))\\ = 2 \sin^2(x/2)(1+2\cos(x) + 2\cos^2(x))$$

Hence, $$f(x) = \dfrac{1- \cos(x) \cos(2x)}{x^2} = \dfrac{2 \sin^2(x/2)(1+2\cos(x) + 2\cos^2(x))}{x^2}$$

$$\lim_{x \to 0} f(x) = \lim_{x \to 0}\dfrac{2 \sin^2(x/2)}{x^2} \times \lim_{x \to 0}(1+2\cos(x) + 2\cos^2(x)) = 2 \times \dfrac14 \times (1+2+2) = \dfrac52$$

share|improve this answer
    
Thank you but I need simpler solution. I can't use the expansion of cos(x). Do you have any idea how to reduce the problem to the limit sin(x)/x? –  Adam Oct 15 '12 at 21:14
1  
@AdamAndersson Your question never indicated any such constraint. Care to revise it? –  Erick Wong Oct 15 '12 at 21:22

Here is a proof using Tools 1-3 below and, I think, nothing else.

Tool 1: $2\cos(a)\cos(b)=\cos(a+b)+\cos(a-b)$.

Tool 2: $1-\cos(a)=2\sin^2(\frac{a}2)$.

Tool 3: Let $u(z)=\frac{\sin(z)}z$, then $u(z)\to1$ when $z\to0$. (You said you knew that.)

Using Tools 1 and 2, one gets $$ \frac{1-\cos x\cos 2x}{x^2}\stackrel{\text{(Tool 1)}}{=}\frac{1-\cos 3x}{2x^2}+\frac{1-\cos x}{2x^2}\stackrel{\text{(Tool 2)}}{=}\frac{\sin^2(x/2)}{x^2}+\frac{\sin^2(3x/2)}{x^2}, $$ hence $$ \frac{1-\cos x\cos 2x}{x^2}=\frac{u^2(\frac{x}2)+9u^2(\frac{3x}2)}4. $$ Now, Tool 3 yields $u(\frac{x}2)\to1$ and $u(\frac{3x}2)\to1$, hence the limit is $\frac{1^2+9\cdot1^2}4=\frac52$.

share|improve this answer

Let's see one line proof:

$$\lim_{x\to 0} \frac{1-\cos x \cos(2x)}{x^2}=\lim_{x\to 0}\frac{1-\cos x }{x^2}+ \lim_{x\to 0}4\cos x\frac{1-\cos 2x }{(2x)^2}=\frac{5}{2}.$$

Chris.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.